Adsorption Kinetics of 137Cs+/90Sr2+ on Ca‐Bentonite: Wang et al. (1st September 2017) - Wang, Rong; Chu, Yingying; Chen, Mengjun
ABSTRACT: : 137 Cs + / 90 Sr 2+ adsorption kinetics on natural Ca‐bentonite under the impact of different adsorption conditions was examined in detail. The results indicate that natural Ca‐bentonite shows a strong adsorption capacity for Cs + /Sr 2+ . The adsorption reached at equilibrium after 2 hours for Cs + . Cs + /Sr 2+ removal efficiency reaches the highest when the pH value is 5 to 8 and increases with the increase of Ca‐bentonite adding amount. Cs + removal efficiency increases with the increase of Cs + initial concentration, while Sr 2+ removal efficiency slightly varies around 70%. The adsorption of Cs + /Sr 2+ by Ca‐bentonite follows the pseudo‐second‐order model and is controlled by chemical adsorption. Meanwhile, the results of intraparticle diffusion modelling indicate that intraparticle diffusion is a kinetics controlling step, besides surface adsorption and liquid film diffusion.